Severity of inducible myocardial ischemia predicts incident acute coronary syndromes in asymptomatic individuals with a family history of premature coronary artery disease - Kral, Brian G.; Becker, Diane M.; Vaidya, Dhananjay; Yanek, Lisa R.; Becker, Lewis C. (Journal of nuclear cardiology, 2012)
Although the severity of inducible ischemia provides incremental prognostic information in persons with known or suspected coronary artery disease (CAD), its significance for predicting long-term CAD outcomes in apparently healthy populations is unknown. This study was designed to evaluate the presence and degree of myocardial ischemia in asymptomatic siblings of persons with premature CAD <60 years of age and to determine its significance for predicting incident acute coronary syndromes (ACS) during follow-up of 5 to 25 years. Siblings (n = 1,287, age 30-59 years, 55% female) were screened for traditional risk factors, underwent exercise treadmill testing with nuclear perfusion imaging, and were followed for the development of ACS (mean follow-up 11.6 ± 5.1 years). The severity of ischemia was assessed by semiquantitative methods using the standard 17-segment model and then categorized by the percent maximal summed stress score as none (0%), minimal (1% to <5%), mild (5% to 10%), moderate (10% to 15%), or severe (≥15%). ACS occurred in 132 subjects (10.3%) and included sudden cardiac death (n = 13), acute MI (n = 62), and unstable angina with revascularization (n = 57). The presence of no (88%), minimal (6%), mild (5%), and moderate/severe (1%) ischemia was associated with an ACS incidence of 8.3%, 19.7%, 25.0%, and 38.9%, respectively (P < .0001 for trend). Kaplan-Meier event-free survival analyses by myocardial ischemia severity categories showed that even minimal and mild myocardial ischemia were associated with greater ACS incidence detectable as early as 2 years after baseline. A Cox proportional hazard model, adjusted for risk factors and follow-up time, showed that each 5% increment in the severity of ischemia resulted in a 77% increase in the hazard of incident ACS (P < .001). Inducible myocardial ischemia is prevalent in asymptomatic siblings of persons with early onset CAD. Most ischemia is minimal or mild in severity, and although the severity of ischemia is associated with the risk of ACS in a graded fashion, the presence of even minimal and mild perfusion defects predicts worse CAD outcomes in this population.